Determinants and Distribution of Waiting Time for First Conception among Ever Married Women in Bangladesh (The Chittagong University Journal of Science, 2022)
Early age at first cohabitation has a major effect on childbearing because women, who marry early, have a longer period of exposure to the risk of becoming pregnant and higher fertility. In a traditional Bangladeshi society it is an urgent need to explore the timing of first conception because it plays a vital role in the determination of reproductive process and fertility. Therefore, the main purpose of this study is to explore meticulously the determinants and distribution of first conception wait among ever married women in Bangladesh, extracting data from Nationally Representative BDHS-2014 data set. In this study the overall first mean conception interval is found to be 19.13±20.80 months with substantial variations by independent variables. The mean time required to conceive for the first time is found relatively low (15.54) among the respondents living in Chittagong division. The mean conception delay is found longer among those who have cohabited below age 15 years (24.36) and shorter (15.57) for the older marriage cohort. The results display that the distribution of first conception wait is positively skewed (β1= 2.22) and leptokurtic (γ2= 6.65). Life table analysis shows that 76% women become conceived within only three years of their first cohabitation. The tri-mean (T) and spread (S) of the first conception interval are found 16 and 24 months respectively. The findings of this study recommend that strict implementation of significant variables-legal age at first marriage; increase the literacy rate, improvement of socioeconomic status and reduction of overweight would be fruitful for normal timing of first conception and further reduction of fertility in Bangladesh.The Chittagong Univ. J. Sci. 43(1): 75-92, 2021